2016
DOI: 10.1108/jpbm-08-2014-0697
|View full text |Cite
|
Sign up to set email alerts
|

The lady doth protest too much: a neurophysiological perspective on brand tarnishment

Abstract: Purpose The purpose of this study is to investigate consumers’ subconscious/emotional responses to brand tarnishment. Design/methodology/approach Brand tarnishment and the responses of business firms in protecting their brands against economic harm have been controversial topics for many years. Unfortunately, those who have resorted to the courts to protect their brands have met with mixed success, mainly because the methodologies used to demonstrate economic harm have proved controversial. One caveat in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This trend has continued in recent years, and, studies using novel data collection methods such as functional magnetic resonance imaging fMRI (Al-Kwifi, 2016;Marques dos Santos et al, 2016), electroencephalography (Boshoff, 2016) and netnography (Hollebeek and Chen, 2014) have been published. The overall goal of introducing new research methods will always be to capture reality in the most accurate way, improve our understanding of why consumers and companies act the way they do and provide better suggestions to managers and policy makers on how to navigate in an ever-changing market reality.…”
Section: From Using Traditional Data Collection and Data Analysis Methods To Introducing New Methodological Approachesmentioning
confidence: 99%
“…This trend has continued in recent years, and, studies using novel data collection methods such as functional magnetic resonance imaging fMRI (Al-Kwifi, 2016;Marques dos Santos et al, 2016), electroencephalography (Boshoff, 2016) and netnography (Hollebeek and Chen, 2014) have been published. The overall goal of introducing new research methods will always be to capture reality in the most accurate way, improve our understanding of why consumers and companies act the way they do and provide better suggestions to managers and policy makers on how to navigate in an ever-changing market reality.…”
Section: From Using Traditional Data Collection and Data Analysis Methods To Introducing New Methodological Approachesmentioning
confidence: 99%
“…Only eight studies identified have combined facial expression analysis or EMG with EEG TF analyses [ 15 , 35 , 36 , 54 , 115 , 203 , 278 ] (Berčík et al 2021). However, this measure provided a useful complement to EEG TF measures, as facial expressions and micro-expressions can separate different emotional responses such as happiness and disgust.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…It provides insight into more than just the current case and in that sense, the case is not the main or only interest of the study. It allows for the development of theoretical or notional tenets, refined through the understanding facilitated by studying the specific case (Dunn, 1996;Yin, 2011). This reflects in this study's interest in offering considerations for marketing managers who endeavour to decolonise customer engagement.…”
Section: Case Study Selectionmentioning
confidence: 95%
“…Case study research has a compelling feature that makes it particularly appropriate for this article: per definition, case studies home in on one or more case(s) that has the potential to offer up new knowledge about real-world behaviour and its meaning (Yin, 2011). As the article has the aim of researching ways in which a brand could decolonise its customer engagement without sacrificing brand legitimacy, studying real-world behaviour is EJM 57,11 necessary.…”
Section: Case Study Selectionmentioning
confidence: 99%